Aging : Some Pleasant Fiscal Arithmetic - Hauner, David (IMF Working Papers; Working Paper ;, 2005)
Projections of age-related public expenditure growth have raised widespread concerns about fiscal sustainability. This paper examines how total expenditure would develop under four policy rules on public expenditure growth. Some simple arithmetic of expenditure, GDP, and population is reviewed and applied in simulations for 19 member countries of the Organization for Economic Cooperation and Development (OECD) over 2000-50. A general and a specific conclusion arise from the results in this paper: Generally, long-term expenditure projections could benefit from revisiting common assumptions on non-agerelated expenditure growth. Specifically, under realistic assumptions, the belt-tightening required to maintain fiscal sustainability under age-related spending pressures could be less painful than commonly thought.